Causas e consequências da variabilidade da hemoglobina glicada numa população pediátrica. - Maria Inês Santos; Catarina Resende; Frederico Rosário; Joana Campos; Graça Carvalho; Cecília Figueiredo (Acta Médica Portuguesa, 2012)
Type one diabetes mellitus is the second most frequent disease in childhood, presenting with serious complications when inadequately controlled. The most useful measure of metabolic control is hemoglobin A1c (HbA1c), being essential the awareness of the causes of its variability.to evaluate the effect of age and time of disease on HbA1c; to evaluate the relationship between HbA1c and serum lipid and microalbuminuria values.Observational, transversal and analytic study, based on data obtained in the files of all patients that attain the Pediatric Diabetic Consult. The studied variables were: sex, actual age, diagnostic age, metabolic control and chronic complications. Statistical analysis was made with Excel2003® and SPSS 15.0®. A significance level of 5% was adopted. Results: a 96 diabetic population was obtained. Last year HbA1c average was 8,3% and was less than 7,5% in one third of the cases. Adolescent's HbA1c (8,4%) was significantly higher than in children (7,8%) (p=0,03). Diabetics with a disease longer than five years presented higher HbA1c values (9% vs. 7,8%; p